Mem-Elements Emulator Design With Experimental Validation and Its Application - Niranjan Raj; Rajeev Kumar Ranjan; Fabian Khateb; Montree Kumngern (IEEE Access, 2021)
An emulator circuit of Memristor, Memcapacitor, and Meminductor commonly termed as mem-elements has been demonstrated in this article. The circuit has been realized using the technique of current mode, which provides better performance over voltage mode counterparts. The current mode analog building blocks, along with a few passive components, have been used in the presented circuit implementation. The fingerprint characteristics have been observed in both simulation and experimental results, validating the theoretical analysis. The robustness of the presented design has been supported by performing different types of analysis like process corner, temperature, and non-volatility behavior. The mem-elements emulator design has been simulated using $0.18~μ \text{m}$ TSMC process parameter, and ±1.2 V power supply has been used. The commercial ICs AD844 and CA3080 are used for the experimental demonstration of the proposed mem-elements design by making a prototype on a breadboard. A layout area of $4829~μ \text{m}^{2}$ , $8098~μ \text{m}^{2}$ , and $8061~μ \text{m}^{2}$ respectively is required for the Memristor, Memcapacitor, and meminductor circuit. The power consumed by the mem-elements circuit is also provided. A chaotic has been implemented using mem-elements to show the usefulness of the emulator design.